Clinical characteristics and treatment outcomes for patients infected with Mycobacterium haemophilum - Pornboonya Nookeu (2020)
© 2019 Centers for Disease Control and Prevention (CDC). All rights reserved. Mycobacterium haemophilum is a nontuberculous mycobacterium that can infect immunocompromised patients. Because of special conditions required for its culture, this bacterium is rarely reported and there are scarce data for long-term outcomes. We conducted a retrospective study at Siriraj Hospital, Bangkok, Thailand, during January 2012-September 2017. We studied 21 patients for which HIV infection was the most common concurrent condition. The most common organ involvement was skin and soft tissue (60%). Combination therapy with macrolides and fluoroquinolones resulted in a 60% cure rate for cutaneous infection; adding rifampin as a third drug for more severe cases resulted in modest (66%) cure rate. Efficacy of medical therapy in cutaneous, musculoskeletal, and ocular diseases was 80%, 50%, and 50%, respectively. All patients with central nervous system involvement showed treatment failures. Infections with M. haemophilum in HIV-infected patients were more likely to have central nervous system involvement and tended to have disseminated infections and less favorable outcomes.